Are Olympic athletes free from cardiovascular diseases? Systematic investigation in 2352 participants from Athens 2004 to Sochi 2014. Issue 4 (30th December 2016) - Pelliccia, Antonio; Adami, Paolo Emilio; Quattrini, Filippo; Squeo, Maria Rosaria; Caselli, Stefano; Verdile, Luisa; Maestrini, Viviana; Di Paolo, Fernando; Pisicchio, Cataldo; Ciardo, Roberto; Spataro, Antonio
Abstract : Context: Olympic athletes represent model of success in our society, by enduring strenuous conditioning programmes and achieving astonishing performances. They also raise scientific and clinical interest, with regard to medical care and prevalence of cardiovascular (CV) abnormalities. Objective: Our aim was to assess the prevalence and type of CV abnormalities in this selected athlete's cohort. Design, setting and participants: 2352 Olympic athletes, mean age 25±6, 64% men, competing in 31 summer or 15 winter sports, were examined with history, physical examination, 12-lead and exercise ECG and echocardiography. Additional testing (cardiac MRI, CT scan) or electrophysiological assessments were selectively performed when indicated. Main outcome measures: Prevalence and type of CV findings, abnormalities and diseases found in Olympic athletes over 10 years. Results: A subset of 92 athletes (3.9%) showed abnormal CV findings. Structural abnormalities included inherited cardiomyopathies (n=4), coronary artery disease (n=1), perimyocarditis (n=4), myocardial bridges (n=2), valvular and congenital diseases (n=45) and systemic hypertension (n=10). Primary electrical diseases included atrial fibrillation (n=2), supraventricular reciprocating tachycardia (n=14), complex ventricular tachyarrhythmias (non-sustained ventricular tachycardia, n=7; bidirectional ventricular tachycardia, n=1) or major conduction disorders (Wolff-Parkinson-White (WPW), n=1; Long QT syndrome (LQTS), n=2). Conclusions: Our study revealed an unexpected prevalence of CV abnormalities among Olympic athletes, including a small, but not negligible proportion of pathological conditions at risk. This observation suggests that Olympic athletes, despite the absence of symptoms or astonishing performances, are not immune from CV disorders and might be exposed to unforeseen high-risk during sport activity.